Exploring Cancer Patients’ and Caregivers’ Perspectives and Knowledge Regarding Biomarker Testing in Canada - Patil Mksyartinian; Selina Xu; Chrissa Barroma; Sandra Peláez; Barry D. Stein (Current Oncology, 2025)
While biomarker testing can provide various benefits for cancer patient outcomes, numerous challenges persist that cause inequities in access across Canada. An online survey consisting of 51 questions was disseminated to evaluate biomarker testing and precision medicine knowledge and experiences from Canadian patients and caregivers. Responses were recorded between June 2023 and January 2024 and assessed various aspects of the biomarker testing experience including the expectations and challenges of patients. Quantitative and qualitative analyses were conducted using Microsoft Excel and R for descriptive and correlative data analysis, respectively. Among the 74 responses, patients reported an overall moderate experience with positive outcomes for those who underwent biomarker testing, including changes to treatment plans and the shrinking of tumours. The main challenges identified included knowledge gaps, a lack of testing availability, turnaround time for results, and financial constraints, all of which contribute to the disparities in biomarker testing access. Qualitative analysis of responses further emphasized a strong patient desire for patient-centred care and collaborative decision-making for biomarker testing options and treatment planning. Addressing these challenges through increased education, policy advocacy, and advancing infrastructure can help to reduce interprovincial inequities in biomarker testing and contribute to improving cancer patient outcomes.